The Effect of Brand Image and Price on Product Purchase Decisions at the Sewing House Akkhwat Makassar - Hasmiati Hasmiati; Ilham Thaief; Muhammad Hasan; Muhammad Dinar; Rahmatullah Rahmatullah (Pinisi Business Administration Review, 2020)
This study aims to determine the effect of brand image and price on product purchase decisions at the Sewing House of Akhwat Makassar. This research is categorized as a type of quantitative descriptive research. The population in this study were all consumers who purchased products at the Makassar Sewing House in July 2019 as many as 101 consumers. Sampling was done by means of purposive sampling of 50 consumers. The method of data collection was done by using interview, questionnaire and documentation techniques. The analysis technique used is multiple linear regression analysis using SPSS 16.0 software. The results showed that the variables of brand image and price partially had a positive and significant effect on product purchasing decisions at the Sewing House for Women in Makassar. Simultaneously, there is a positive and significant influence between brand image and price variables on product purchasing decisions at the Sewing House for Women in Makassar.